Historical geography of Torgay and Sulduz based on the book of Safwat al-Safa - Fatemeh Jafarniya; Mohammad AzizNejad (اکولوژی انسانی)
Geographical places are the basis for the formation of historical events, and the names of these places reflect the culture and historical realities of each region; Therefore, based on the names recorded in the texts and sources, it is possible to investigate the background of a region. For example, in the book Safwat al-Safa authored by Ibn Bazzaz Ardabili, the names of the regions are mentioned, by referring to them, a brief picture of the historical geography of some regions of Azerbaijan such as Torgay and Sulduz can be presented. Torgay and Sulduz were the names of the provinces in the Azerbaijan region, where Shaykh Safi al-Din Ardabili (650-735 AH/1335-1252AD) met with the people of those provinces during the rule of Abu Said (717-736 AH/1317-1335 AD), Ilkhan Mongol. In the historical and geographical texts and sources, there is no mention of the nomenclature, history and geographical scope of these provinces. Considering this issue, this research tries to reconstruct and examine the historical geography of Torgay and Sulduz provinces and their importance using the book of Safwat al-Safa and the historiography of the Mongol and Timurid periods with a descriptive-analytical approach. The findings of the research indicate that Torgay province is located in the southeast and Sulduz province are located in the south and southwest of Lake Urmia, and due to having a favorable climate and consequently abundant water and fertile soil, it is one of the most populated areas of Azerbaijan. The period of rule was considered to be the Mongol patriarchs. Also, the inhabitants of these Sunni provinces were considered Turkic and Mongol tribes and followers and disciples of Shaykh Safi al-Din Ardabili.